2022
DOI: 10.3390/biomedicines10020308
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Gut Microbiota and Diabetes Mellitus, and Treatments for Diabetes Mellitus

Abstract: Diabetes mellitus is considered to be a global epidemic. The combination of genetic susceptibility and an unhealthy lifestyle is considered to be the main trigger of this metabolic disorder. Recently, there has been increased interest in the roles of gut microbiota as a new potential contributor to this epidemic. Research, in recent years, has contributed to an in-depth characterization of the human microbiome and its associations with various diseases, including metabolic diseases and diabetes mellitus. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 143 publications
(124 reference statements)
0
20
0
2
Order By: Relevance
“…Understanding how the microbiota interacts with immune cells to create immune tolerance could enable the development of new therapeutic strategies for T1DM and improve the quality of life of people with T1DM. It is worth noting that some studies indicate the influence of dysbiosis on the occurrence of various types of diabetes: T1DM, T2DM, and T3DM [71, 215,216]. Diabetes changes the composition of the microbiota, and the altered microbiota affects the pathophysiology of the disease.…”
Section: Perspectivesmentioning
confidence: 99%
“…Understanding how the microbiota interacts with immune cells to create immune tolerance could enable the development of new therapeutic strategies for T1DM and improve the quality of life of people with T1DM. It is worth noting that some studies indicate the influence of dysbiosis on the occurrence of various types of diabetes: T1DM, T2DM, and T3DM [71, 215,216]. Diabetes changes the composition of the microbiota, and the altered microbiota affects the pathophysiology of the disease.…”
Section: Perspectivesmentioning
confidence: 99%
“…Many studies in recent years have suggested that diabetes is closely associated with PC. Type 2 diabetes is often accompanied by moderate intestinal dysbiosis, which is characterized by increased numbers of Lactobacillus , Bacteroidetes and Proteobacteria and reduced abundance of Faecalibacterium prausnitzii and Firmicutes ( Craciun et al., 2022 ) . The gut microbiota affects diabetes by affecting body mass, bile acid metabolism, chronic inflammation, insulin resistance and gut hormone regulation ( Ren et al., 2017 ).…”
Section: Risk Factors For Pc In Relation To the Gut Microbiotamentioning
confidence: 99%
“…Studies of the human microbiome have revealed its important implications on the human body and the pathogenesis of a variety of diseases [ 15 , 16 ]. While early studies of the microbiome focused primarily on the interactions of gut flora with innate phenotypes [ 17 , 18 ], novel studies have characterized the microbiome as an important driver of various diseases, including inflammatory bowel disease (IBD) [ 19 , 20 ], arthritis [ 21 , 22 ], Alzheimer’s [ 23 , 24 ], diabetes [ 25 , 26 ], cardiovascular disease [ 27 , 28 ] and cancer [ 29 ]. The intratumor microbiome in cancer has emerged as an important player in mediating effective immune response, treatment efficacy, and cell survival through the production of metabolites and downstream interactions within the tumor microenvironment [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%